PREVALENCE OF CARPAL TUNNEL SYNDROME AMONG OFFICE WORKERS IN TWIN CITIES - Amush Shah, Syeda; Saeed, Mahnoor; Maqsood, Fatima; Hamza, M. Ameer; Khan, Shumaila; Rafique, Nazish (Annals of Allied Health Sciences, 2024)
Objective: To determine the prevalence of carpal tunnel syndrome (CTS) among office workers in twin cities. Material & Methods: This was a cross-sectional study that used a non-probability purposive sampling technique to select 134 participants based on predefined inclusion criteria. The frequency of CTS was determined using the Phalen and Tinel test. The Boston Carpal Tunnel Questionnaire (BCTS) was used to evaluate the participants' functional status and severity, and the Numeric discomfort Rating Scale (NPRS) was used to measure their discomfort. SPSS 23 was employed for the purpose of data analysis. Results: Out of the 134 participants, 80% identified as male and 20% as female. The participants' mean service time was 7.14 ± 8.9 years, and their mean age was 29.6 ± 7.7 years. Employees who work 8.6 ± 2.9 hours a day are more likely to have CTS. According to positive Tinel tests, the prevalence was 13.4%, and Phalen tests showed a prevalence of 25.4%. The Phalen and Tinel tests had positive frequency rates of 25.4% and 13.4%, respectively, with the right hand being the dominant hand (87.3%). The symptoms severity score (SSS) of 1.32 ± 0.48 and a functional status score (FSS) of 1.32 ± 0.55 on the Boston Carpal Tunnel Questionnaire. Conclusion: This study found that office workers had a higher likelihood of having CTS, with a prevalence of 25.4% for positive Phalen tests and 13.4% for positive Tinel tests.